Effect of Eyes Open/Closed on Plantar Pressure during Static Balance Evaluation - Qiang LIN; Wude CHEN; Yuxin ZHENG; Wanchen LIAO; Haidong HUANG; Haining OU; Junjie LIANG (康复学报)
Objective:To evaluate the effect of visual input on static balance function, by assessing the posture control of young healthy subjects with eyes open and closed using the plantar pressure analysis technique.Methods:A total of sixty-six young, healthy adults were recruited in the study. They were instructed to stand at a fixed position on the FreeMed plantar pressure analysis test board. The subject's pelvis was swung in four directions including front, back, left and right, to make their foot pressure evenly distributed. The pressure data of the soles was recorded in eyes open and closed states for 30 seconds, respectively. The collected data was processed using the Freestep plantar pressure analysis system. The ball length, ellipse area, average velocity, average X, average Y, ellipse tilt angle, ellipse eccentricity, maximum swing, minimum swing, and total plantar load, forefoot load, and hind foot load of the left and right lower limbs were obtained.Results:There were significant differences in the ellipse area (P< 0.05), the average Y(P< 0.001) and the maximum swing (P< 0.001) of the subjects in the two states of eyes open and closed. Compared with eyes open condition, the ellipse area decreased, the average Y decreased, and the maximum swing increased during eyes closed condition. According to the scatter plot distribution of center of pressure (COP), it was found that the COP distribution was more concentrated with the eyes open than that with eyes closed. Comparing the two conditions (eyes open and eyes closed), the subjects'left foot forefoot load (P< 0.001), right foot forefoot load (P< 0.001), left foot hind foot load (P< 0.001) and right foot hind foot load (P< 0.001) were significantly different. Compared with the eyes open, the left-foot forefoot load and the right-foot forefoot load increased both, while the left-foot hind foot load and the right-foot hind foot load decreased. In the comparison of the two status of the left lower limb and the right lower limb, the subject's overall load on the left foot in the eyes open state was reduced compared with the right lower limb (P=0.030); the overall load on the left foot was also lower than that on the right side in eyes closed. The difference of the lower limbs decreased was statistically significant (P=0.021). In the comparison of the forefoot and hind foot in eyes open and closed, the hind foot load was significantly greater than the forefoot load (P< 0.001).Conclusion:The findings of this experiment indicated that normal young subjects could adjust the balance function under different visual input status by changing the ellipse area and swing amplitude. The kinematics and dynamics parameters analyzed by plantar pressure analysis can be used for quantitative and clinical evaluation of static balance function.